The Utilization of Effective Microorganism 4 (EM4) on Growth of Oil Palm Seedling in Pre Nursery - Dwi Astutik; Ratih Rahhutami; Aline Sisi Handini; Ahmad Sutopo (International Journal of Multi Discipline Science, 2020)
A planting medium that rich in nutrients is needed for oil palm, especially in the nursery phase. This study aimed to determine the effect of various doses of EM4 and to get the best dose of EM4 on the growth of oil palm seedlings in the pre-nursery. The research method used was a non-factorial completely randomized design with 4 treatments, namely 0 ml EM4 (A1), 4 ml EM4 (A2), 8 ml EM4 (A3), and 12 ml EM4 (A4). Each treatment was repeated 6 times so that there were 24 experimental units. The data obtained were analyzed for variance at the 5% level, if the effect was real, it was followed by the least significant difference (LSD) test. Based on the results of the study, it could be concluded that application of various EM4 doses had a significant effect on plant height (4-12 MST), the number of leaves (4-8 MST), trunk girth (4-12 MST), and shoot wet weight but did not significantly affect the number of leaves (12 MST), the volume of roots, length of roots, root wet weight and shoot dry weight, dry weight root, the best dose was shown at a dose of 12 ml EM4.